2000
DOI: 10.1002/1438-9312(200010)102:10<618::aid-ejlt618>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the tocopherol and fatty acid contents in rapeseed oil during refining

Abstract: Among the most important metabolic compounds there are some which are not synthesized by human and animal organisms and have to be supplied in appropriate quantities in due time. Vitamin E and the essential unsaturated fatty acids have crucial physiological significance, and their greatest quantities occur in plant oils. During refining, apart from unnecessary substances, nutritionally advantageous compounds are also being eliminated. In the present paper changes of tocochromanols taking place during refining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 10 publications
(10 reference statements)
0
21
0
Order By: Relevance
“…Lecithin from squid viscera may contain small amounts of natural antioxidants that might be one of the causes of its higher oxidative stability. Gogolewski and others (2000) also reported that long chain polyunsaturated fatty acids which esterified with polar lipids had synergistic effects with antioxidants. High oxidative stabilities of lecithin from animal and plant sources were also reported by using different methods (Palacios and Wang 2005; Wang and Wang 2008; Belhaj and others 2010).…”
Section: Resultsmentioning
confidence: 97%
“…Lecithin from squid viscera may contain small amounts of natural antioxidants that might be one of the causes of its higher oxidative stability. Gogolewski and others (2000) also reported that long chain polyunsaturated fatty acids which esterified with polar lipids had synergistic effects with antioxidants. High oxidative stabilities of lecithin from animal and plant sources were also reported by using different methods (Palacios and Wang 2005; Wang and Wang 2008; Belhaj and others 2010).…”
Section: Resultsmentioning
confidence: 97%
“…The content of a-tocopherol in extracted fat was determined by HPLC (Gogolewski, Nogala-Kałucka, & Szeliga, 2000). The HPLC system consisted of the Waters Model 600 gradient pump, fluorimetric detector and Waters Milleniumdata acquisition system.…”
Section: A-tocopherolmentioning
confidence: 99%
“…It maintain natural beneficial ingredients of sesame oil such as tocopherols, sterols, carotenoids, and phospholipids which are partially removed as a result of oil refining (Gogolewski et al,2000;Koski et al, 2003). Considering of the growing concern and demand about the functional and nutritional properties of oils, the present work was therefore designed to evaluate and compare the fatty acid composition of oil extraction methods of some Turkish sesame genotypes.…”
Section: Introductionmentioning
confidence: 99%